TAMAN AIR RAMAH ANAK DI KOTA PELAIHARI - Basri, Nurgisdarani; Rahman, Akbar (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The Child Friendly Water Park in Pelaihari City is designed with Child Friendly Playroom Standards so that children can play safely and comfortably, and learn to recognize water from an early age. The method used in this design is "Behavioral Architecture" with children's behavior as the main design consideration. The design approach uses a "Psychological Approach" with child psychology as the main approach in this design. Considering the number of visitors who come, the concept of the program used is "Flexibility". Garden elements and spaces are made with various functions and forms following a predetermined program concept. It is hoped that with this park children can play safely and comfortably and can learn to recognize water from an early age with fun.